The efficacy of chlorine depuration in detoxifying mussels (P. viridis) contaminated with paralytic Shellfish Poisoning (PSP) toxins from pyrodinium bahamense var. compressum - Genesera, Josefina A.
Mussels contaminated with paralytic shellfish poison (PSP) toxins were detoxified using a flow-through depuration system of 0.1 ppm residual chlorine. Survival rate, presence or absence of public health significant (PHS) organisms, changes in trimethylylamine (TMA), total volatile nitrogen base (TVN-N0 and hypoxanthine (Hx) as well as sensory qualities were also monitored every six hours for a period of 24 hours. A high survival rate for physiologically active mussels were obtained during depuration. Public health significant organisms such as V. cholera, Shigella, Salmonella and E.coli were likewise absent. However, V. parahaemolyticus was still detected even after 24-hour depuration. TMA and TVB-N contents changed with depuration time. No definite pattern could be established for Hx and depuration time. The same relationship occurred between depuration time and sensory qualities of depurated mussels. T-test on sensory qualities between mussels in the experimental and in the control groups showed no difference at 5% level of significance. Detoxification of PSP toxin present in mussel meat through the depuration process depends largely on the physiological activity of the mussels. The high and low concentration of PSP toxin did not render the mussel free from poison after 24 hours depuration. However, when mussels are physiologically active, a value lower than the threshold level (400 MU/100 g sample) can be achieved in 43.5 hours or one day and 19.5 hours. The zero level concentration can be achieved after 46.5 hours or one day and 22.5 hours.